(untitled) (Research, Society and Development, 2022)
In view of the needs of water supply, in schools and communities, in the region of islands and floodplains of the municipality of Abaetetuba, rainwater supply systems were installed through the Cisterns in Schools program. The objective of this work was to investigate the usability of rainwater collection and storage systems implemented through the "Cisterns in Schools" Program in island communities and abaetetuba floodplains, as an alternative for water supply. The research was configured as qualitative, based on a field study with the application of forms and on-site visits to feed the field diary. The results showed that 96% of the informants claim to have received training for the maintenance of the systems, and 74% reported that they exclusively use rainwater for consumption in schools. However, the field diary data differs from this information because it has been identified that many systems are inoperative, or the community uses other water sources for consumption.